Through the Looking Glass: Exploring the Relationship Between Nonverbal and Verbal Behaviour on Rapport and Dyadic Cooperation - Weiher, Lynn (Cranfield University, 2017)
Poster presented at the 2017 Defence and Security Doctoral Symposium.This research programme wishes to explore the relationship between verbal and nonverbal behaviour, rapport, and dyadic cooperation. Although researchers have long recognised the complementary roles that verbal and nonverbal behaviour play in interaction, we know little about how verbal and nonverbal mimicry co-occur, nor how these relate to the established outcomes of rapport (internal perception) or cooperation (external behaviour).In this study, dyads engage in short interview-style interactions where the interviewee has different goals (e.g., guilty vs. non-guilty knowledge, being cooperative vs. non-cooperative) to examine how these motivations effect not only nonverbal mimicry but also verbal and emotional mimicry.
Keywords: 'Mimicry'; 'Rapport Building'; 'Nonverbal behaviour'; 'DSDS17'; 'DSDS17 poster'; 'Language; Communication and Culture not elsewhere classified'; 'Psychology and Cognitive Sciences not elsewhere classified'